Exploring Kawayan Dialect Lexicon (Wordlist) in Southern Negros, Philippines - John Gerald Arbias Pilar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The extent of lexical research has resulted in the development of word lists, which have to rely on consideration of code-glosses and their alternative words to understand their meaning and the status of these forms. This research tries to describe the Kawayan dialect lexicon from a list of 278 words that are more easily traced to the Bisayan family and appear to be Western Bisayan by utilizing and manipulating an Excel Pivot Table to trace timestamps to extract words from informants (native speakers). The research was submitted for cross-checking between coders to be reviewed and checked for validity and reliability as a protocol for verifying the accuracy of data collection from native speakers. This word list is essential in providing information about the genetic relationship of the Kawayan dialect to the Filipino language group. Additionally, digging deeper into how this research is presented and disseminated to its intended readers and scholars is productive and eye-opening. Since this is a pioneering investigation and documentation of the Kawayan dialect, although it may be annoying, at least it started as one of the distinctive features of other dialects yet to be included in the list of Filipino dialects. Researchers today urge us to explore and investigate this dialect before it disappears.